Sinology in Seattle: The University of Washington and its Influence on the Study of Chinese Medicine - Sean Bradley (Wolters Kluwer Health/LWW, 2021)
The University of Washington has played a pivotal role in the field of sinology with faculty and alumni producing major publications in Chinese history, literature, phonetics, and linguistics. These contributions have been instrumental in the development of sinology as a field and have both directly and indirectly influenced the study of Chinese Medicine. By tracing the history of the Department of Asian Languages and Literature and examining several major figures, we can better understand how these individuals shaped the development of Chinese Medicine and contributed to its spread worldwide.